Unlocking the Potential: The Islamic Finance Social Impact Assessment - Kuanova, L.A.; Zhangabayev, N.; Kenzhegulova, G.K. (BUKETOV BUSINESS REVIEW, 2024)
Object: The rise of Islamic finance, which involves financial instruments operating within the ethical and shariah principles framework and adopted by financial institutions, gains momentum in main global markets. This trend is driv en by a new global reality where long-term development cannot occur without addressing deepening social contradic tions and ethical norms and Islamic finance’s sustainable approach plays vital role. This article aims to assess the Islam ic finance social impact and evaluate the covering resource shortfall and poverty reduction through social tools. Methods: The methodology of the research is based on the empirical methods and examination of the correlation between the country's potential Islamic financial assets, the estimated zakat collection and the coverage of resource shortage. Findings: The findings have practical implications for the country's socio-economic development. The authors have empirically assessed the resources Kazakhstan requires to cover poverty in the share of the gross domestic prod uct, and the resource gap for poverty reduction. Furthermore, the authors have evaluated the potential zakat collection of the country. Conclusions: It is suggested that the potential zakat collection can impact the poverty reduction process and ad dress deepening poverty indicators within the country. The zakat institution possesses the capacity to provide support to the impoverished population and potentially reduce government expenditure required to enhance the socially vulnerable population welfare.